2016
DOI: 10.18227/1982-8470ragro.v10i2.2760
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de sementes de soja obtidas de diferentes cultivares submetidas à dessecação com diferentes herbicidas e épocas de aplicação

Abstract: A dessecação é uma técnica utilizada pelos produtores de soja com o objetivo de antecipar a colheita. No entanto, para a produção de sementes essa técnica necessita de cuidados, uma vez que alguns dessecantes podem deixar resíduos na semente prejudicando sua qualidade. Objetivou-se com esse estudo avaliar o efeito da aplicação de dessecantes em diferentes épocas sobre a qualidade fisiológica de sementes, após seis meses de armazenamento, de cultivares de soja com diferentes teores de lignina no tegumento. As p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
8
0
4
Order By: Relevance
“…Pereira et al (2015a) demonstraram que a aplicação de diferentes dessecantes nos estádios R7.1 e R7.3 proporcionaram maior percentual de germinação quando comparado a testemunha. Em contrapartida, outros trabalhos determinam que o uso de herbicidas para a dessecação das plantas, com a finalidade de produção de sementes, em geral, resultaram em redução do percentual de germinação, sendo essa redução depende da cultivar e do herbicida utilizado (DELGADO et al, 2015;BOTELHO et al, 2016).…”
Section: G: Germination (%); F: Vigor By the Cold Test (%); Ea: Vigorunclassified
“…Pereira et al (2015a) demonstraram que a aplicação de diferentes dessecantes nos estádios R7.1 e R7.3 proporcionaram maior percentual de germinação quando comparado a testemunha. Em contrapartida, outros trabalhos determinam que o uso de herbicidas para a dessecação das plantas, com a finalidade de produção de sementes, em geral, resultaram em redução do percentual de germinação, sendo essa redução depende da cultivar e do herbicida utilizado (DELGADO et al, 2015;BOTELHO et al, 2016).…”
Section: G: Germination (%); F: Vigor By the Cold Test (%); Ea: Vigorunclassified
“…In this context, seeds from soybean plants desiccated at more advanced reproductive stages presented higher magnitudes for germination percentage, in relation to the desiccation carried out in the phenological stages R6.0, R7.1 and R7.2, research confirms the results obtained and they define that in these stages there is compromise in the germination of soybean seeds (Kappes et al, 2009;Ferrari et al, 2016). In general, the use of pre-harvest desiccation herbicides focused on seed production practices results in negative effects to the percentage of germinated seeds and attributes that there is variation between the tested genotypes and the desiccant herbicide (Delgado et al, 2015;Botelho et al, 2016). The charac the phenol that the ex (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…According to Botelho et al (2016), preharvest desiccation can affect the seed vigor probably because of the effect of herbicides on the integrity of seed cell membranes, affecting the solute release rate, which is indirectly detected by the electrical conductivity test. This decreases the capacity of reorganization of membranes, resulting in a higher loss of solutes to the environment and in seeds with lower uniformity and germination speed and stimulating the development of pathogenic microorganisms (MARCOS FILHO, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Negative effects were also found for the diquat herbicide, which presented lower results than the control treatment for the variables GE, FGC, EM, and AA (Table 4). In addition, Botelho et al 2016 found that the physiological quality of soybean seeds after six months of storage decreased because of the use of diquat for pre-harvest desiccation. Table 4.…”
Section: Methodsmentioning
confidence: 99%